2015
DOI: 10.4067/s0718-27242015000200002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regional Innovation Systems (RIS) in Translating R&D Investments into Economic and Employment Growth

Abstract: The emergence of the so-called "European Paradox" shows that increasing Governmental R&D Investment is far from being a 'panacea' for stagnant growth. It is worth noting that Governmental R&D Investment does not have a statistically significant impact on employment, indicating the need to assess the trade-offs of policies that could lead to significant increases in government expenditure. Surprisingly, Governmental R&D Employment does not contribute to 'mass-market' employment, despite its quite important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
12
0
5
Order By: Relevance
“…Process innovation, in its turn may promote gains in productivity (Terjesen & Patel, 2017) and enables cost reduction by implementing improvements in the production process (Moutinho, Au-Yong-Oliveira, Coelho, & Manso, 2015). Radical innovations even have the power to change the whole industry, by transforming new ventures in industry leaders and moving incumbents out (Hill & Rothaermel, 2003;Schoenmakers & Duysters, 2006).…”
Section: Innovation Performance and Financial Performancementioning
confidence: 99%
“…Process innovation, in its turn may promote gains in productivity (Terjesen & Patel, 2017) and enables cost reduction by implementing improvements in the production process (Moutinho, Au-Yong-Oliveira, Coelho, & Manso, 2015). Radical innovations even have the power to change the whole industry, by transforming new ventures in industry leaders and moving incumbents out (Hill & Rothaermel, 2003;Schoenmakers & Duysters, 2006).…”
Section: Innovation Performance and Financial Performancementioning
confidence: 99%
“…Similar findings were achieved by Heidenreich (2009) in a study of 270 regions from 27 European countries. Moutinho et al (2015), in an empirical study of 158 regions from 18 European countries, identified that technological capacity enhancement, which is strongly related to the innovation capacity of the whole region, is effective for reducing unemployment without threatening sustainable economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mechanism that allows this contribution is the knowledge spillover that occurs from the firm or the network of firms that invested intensely on R&D for the local industries they compete and for the region as a whole. It expands the opportunities related to technology and leverages the capacity to recognize and exploit new business opportunities in general (MOUTINHO et al, 2015). One common way innovative regions organize itself and its RIN is by clusters specialized in one or some closely related industrial sector (GIULIANI;BELL, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations may take the initiative in relation to the discontinuity -that means they can actively try to create those changes, thus "rewrite the rules of the competitive match". Studies have shown that smallest companies have a need to develop a strategic orientation and routines that will help them to cope not only with the "steady-state" of innovation, but also with a discontinuous innovation at the same time (Moutinho1, R., et. al., 2015).…”
Section: The Implementation Of Systematic Changementioning
confidence: 99%